IMPROVING STUDENTS’ READING COMPREHENSION OF PROCEDURE TEXT THROUGH PICTURE WORD INDUCTIVE MODEL STRATEGY - Militansina, .; ., Ikhsanudin; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The research was intended to improve the students’ reading comprehension of procedure text through Picture Word Inductive Model strategy. It was a classroom action research which was conducted for the purpose to solve the students’ interest and participation including the reading comprehension problems that happened in the classroom and to improve the teaching-learning process. Based on the research findings, the students’ learning had been improved; the students were more interested in learning and they liked to participate interactively in the classroom activity. They enjoyed the activities and cooperated with each other. Thus, building self-confidence and cooperative character were considered as the other strengths in applying PWIM strategy. Moreover, the students improved their reading comprehension on communicative purpose, supporting details, implicit information, vocabularies, and referent. Based on the research findings, the students’ mean score in the first cycle was 65.5 (average to good) and in the second cycle was 83 (good to excellent). Keywords: Picture Word Inductive Model, Procedure Text, Reading Comprehension Abstrak: Penelitian ini bertujuan untuk meningkatkan pemahaman membaca siswa pada teks prosedur melalui strategi Picture Word Inductive Model. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dengan tujuan untuk menyelesaikan permasalahan minat, partisipasi siswa dan termasuk permasalahan dalam pemahaman membaca yang terjadi di kelas serta untuk meningkatakan proses belajar mengajar. Berdasarkan hasil temuan penelitian, belajar siswa telah meningkat; siswa menjadi lebih tertarik untuk belajar dan mereka suka berpartisipasi secara interaktif dalam beraktivitas di kelas. Mereka merasa nyaman melakukan aktivitas-aktivitas dan saling berkerjasama. Hal itu, membangun percaya diri dan karakter kooperatif yang dijadikan sebagai kekuatan dalam menerapakan strategi Picture Word Inductive Model (PWIM). Selain itu, siswa mengalami peningkatan pemahaman membaca mereka diantaranya dalam aspek tujuan komunikatif, detail pendukung, informasi implisit, kosakata, dan referensi. Berdasarkan temuan penelitian, rata-rata nilai siswa pada siklus pertama adalah 65,5 (sedang-baik) dan di siklus kedua adalah 84 (baik-sangat baik). Kata Kunci: Strategi Picture Word Inductive Model, Teks Prosedur, Pemahaman Membaca